Professorial Entrepreneurial Research: An Innovative and Comprehensive “Tri–Analytics Engine” via “Triodynamics” that uses In-Depth Triostatistics to Establish a Longitudinal Faculty Research Agenda - Osler II, James Edward Osler II (Advances in Social Sciences Research Journal, 2021)
The narrative in this paper provides an in-depth, novel, and innovative methodology to aid higher education faculty in the production of an innovative research agenda designed to trichotomously sustain, advance, and prolong their existing careers. The methodology used to do the aforementioned is referred to as the “Tri–Analytics Engine”. A “Tri–Analytics Engine” is a pioneering initial and accumulative advanced post hoc research practice grounded in Triostatistics. The Tri–Analytics Engine has an introductory methodology termed “Triodynamics” as starting foundational “base research operation” that sets the stage for future research efforts that have their foundation in the initial research topic. Triodynamics are a set of three trichotomous standards that aid the investigator in the creation of a post hoc research agenda after the primary Tri–Analysis analytic. A Tri–Analytics Engine is also a personal entrepreneurial inquiry-based ethos that is trichotomously complex, comprehensive, and cumulative that has Triostatistics at its core.